Bioactive Components of Seaweed Eucheuma cottonii Potential as Antibacteria - Aisyah Astriani; Nurjanah Nurjanah (Jurnal Biologi Tropis, 2023)
Indonesian waters are rich in biological resources of seaweed, one of which is seaweed Eucheuma cottonii. However, its use is still limited for the process of making various foods such as food thickeners, stabilizers and forming food gels. Even though it's seaweed Eucheuma cottonii has a much more important role, namely containing bioactive components that can function as antibacterials that are beneficial to human health. The aim of this research is to identify the various bioactive components of seaweed Eucheuma cottonii which has potential as an antibacterial. This research method uses a descriptive exploratory method by collecting information from various previous research literature, both from national and international journals and databases online like Researchgate, Google Scholar, and Directory of Open Access Journals. The results of this study indicate the active components of seaweed Eucheuma cottonii contains alkaloids, saponins, steroids, flavonoids, and polyphenols soil which can function as an antibacterial against gram-negative and gram-positive bacteria such as E. coli, Staphylococcus aureus, Streptococcus mutans, Bacillus cereus, Salmonella typhi, Pseudomonas aeruginosa, Vibrio cholera and Proteus mirabilis. In order for the bioactive components of seaweed to function effectively as an anti-bacterial, it is better to use a higher concentration of seaweed extract.